1979
DOI: 10.1007/bf00118714
|View full text |Cite
|
Sign up to set email alerts
|

Counterflow in rotating superfluid helium

Abstract: We have observed a variety of effects involving thermal counterflow in rotating superfluid helium. In particular, the temperature and chemical potential gradients associated with the motion of vortex lines have been measured. The two-fluid equations for helium in rotation have been solved for channel flow in a channel of finite height and the results are compared with our data. Interesting effects associated with the onset of turbulence and with the onset of vortex line depinning are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Following a similar line of reasoning, Yarmchuk and Glaberson (1979) questioned whether one could rely on the Bekarevich-Khalatnikov condition at all. This caution is entirely justified in the region where the onset of depinning occurs.…”
Section: Ivd)mentioning
confidence: 99%
“…Following a similar line of reasoning, Yarmchuk and Glaberson (1979) questioned whether one could rely on the Bekarevich-Khalatnikov condition at all. This caution is entirely justified in the region where the onset of depinning occurs.…”
Section: Ivd)mentioning
confidence: 99%
“…But if vortices are pinned, in a boundary layer of width k~ -~ -k~ ~ superfluid velocities as well as displacements rL and angles drL/dz increase proportionally to d. One might expect that the onset of depinning would be determined by the condition that one of these quantities reaches some critical value independent of bulk properties. 3 In this case the critical mean flow density for depinning should be inversely proportional to d. But the experiment shows 3 that the critical density flow is inversely proportional to x/d. Probably this suggests that some sort of bulk turbulence has an effect on the onset of depinning.…”
Section: Vt~vxt+ivytmentioning
confidence: 99%
“…1'2 The direct measurement of the temperature gradients in stationary thermal flow also has been recently done. 3 The theory of mutual friction has been developed following the ideas of the pioneering paper by Hall and Vinen 1"4-6 (for additional references see Refs. 3 and 6).…”
Section: Introductionmentioning
confidence: 99%
“…As AJL^ -> 0, \v n -v s \ must drop below the critical value before A^ = 0. Measurements and theory have shown that when the L-K equations apply, Vju = 0 [4]. Further inspection of the nonlinear term shows that v s does not have an entrance region because v s -Vv s <x Vv s 2 and a steady state solution would not produce a constant mass flow averaged over a cross section.…”
Section: The Problemmentioning
confidence: 97%
“…The thermodynamic variables are the temperature, pressure and entropy: T, p, and s. The gravitational acceleration is g and c p is the specific heat. We have simplified equation (4) for the conservation of entropy by removing the pressure dependence of s and the thermal conductivity of He II, both of which are negligible for our application. We omitted the second viscosity terms of Khalatnikov since they are negligible in steady flow.…”
Section: The Problemmentioning
confidence: 99%